Estudio del manejo avanzado de heridas contaminadas en caninos - Santa Cruz Espinoza, Stefannie Gabriela (2022)
This document was developed with the purpose of strengthening knowledge regarding the study of advanced management of contaminated wounds in dogs. Wound repair is not only a challenge in human medicine, we also have veterinary medicine. There are many factors that affect the time of wound closure, once the wound has been thoroughly evaluated, the first decision to make is whether to close the wound or not. If there is any question as to the degree of contamination, the possibility of deep injury, damaged or delayed tissue, tissue viability, or blood vessels, the wound assessment should be repeated at closure considered. Highly contaminated patients with wounds or extensive tissue damage are at high risk for dehiscence unless appropriate initial wound care is performed. In clinical practice in canines, wounds such as lacerations, avulsions, punctures and incisions are frequently observed. Understanding the etiological mechanisms that create the wounds allows us to determine the extent of the injury in terms of the degree of contamination present in it, these mechanisms are key factors to guide the treatment and the type of closure used. In canines, where the avulsion is usually caused by a car accident, the wound usually has a considerable amount of highly contaminated necrotic tissue. On the other hand, it is important for practitioners to understand the phenomenon of tissue scarring and how it is negatively affected when medications, especially disinfectants, are used non-technically.